Factors associated to infection by Toxoplasma gondii in pregnant women attended in Basic Health Units in the city of Rolândia, Paraná, Brazil - Dias, Renata Cristina Ferreira; Lopes-Mori, Fabiana Maria Ruiz; Mitsuka-Breganó, Regina; Dias, Rafael André Ferreira; Tokano, Deise Vieira; Reiche, Edna Maria Vissoci; Freire, Roberta Lemos; Navarro, Italmar Teodorico (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The aim of the present work was to determine the prevalence of IgG and IgM anti-Toxoplasma gondii antibodies and the factors associated to the infection in pregnant women attended in Basic Health Units in Rolândia, Paraná, Brazil. The sample was divided in two groups: group I (320 pregnant women who were analyzed from July 2007 to February 2008) and group II (287 pregnant women who were analyzed from March to October 2008). In group I, it was found 53.1% of pregnant women with IgG reactive and IgM non-reactive, 1.9% with IgG and IgM reactive, 0.3% with IgG non-reactive and IgM reactive and 44.7% with IgG and IgM non-reactive. In group II, it was found 55.1% with IgG reactive and IgM non-reactive and 44.9% with IgG and IgM non-reactive. The variables associated to the presence of IgG antibodies were: residence in rural areas, pregnant women between 35-40 years old, low educational level, low family income, more than one pregnancy, drinking water which does not originate from the public water supply system and the habit of handling soil or sand. Guidance on primary prevention measures and the quarterly serological monitoring of the pregnant women in the risk group are important measures to prevent congenital toxoplasmosis.